Identification of synaptic targets of Drosophila pumilio. - Gengxin Chen; Wanhe Li; Qing-Shuo Zhang; Michael Regulski; Nishi Sinha; Jody Barditch; Tim Tully; Adrian R Krainer; Michael Q Zhang; Josh Dubnau (PLoS Computational Biology)
Drosophila Pumilio (Pum) protein is a translational regulator involved in embryonic patterning and germline development. Recent findings demonstrate that Pum also plays an important role in the nervous system, both at the neuromuscular junction (NMJ) and in long-term memory formation. In neurons, Pum appears to play a role in homeostatic control of excitability via down regulation of para, a voltage gated sodium channel, and may more generally modulate local protein synthesis in neurons via translational repression of eIF-4E. Aside from these, the biologically relevant targets of Pum in the nervous system remain largely unknown. We hypothesized that Pum might play a role in regulating the local translation underlying synapse-specific modifications during memory formation. To identify relevant translational targets, we used an informatics approach to predict Pum targets among mRNAs whose products have synaptic localization. We then used both in vitro binding and two in vivo assays to functionally confirm the fidelity of this informatics screening method. We find that Pum strongly and specifically binds to RNA sequences in the 3'UTR of four of the predicted target genes, demonstrating the validity of our method. We then demonstrate that one of these predicted target sequences, in the 3'UTR of discs large (dlg1), the Drosophila PSD95 ortholog, can functionally substitute for a canonical NRE (Nanos response element) in vivo in a heterologous functional assay. Finally, we show that the endogenous dlg1 mRNA can be regulated by Pumilio in a neuronal context, the adult mushroom bodies (MB), which is an anatomical site of memory storage.